The Early learning accomplishment profile for developmentally young children birth to 36 months - Glover, M. Elayne; Preminger, Jodi L.; Sanford, Anne R.
Assessment instrument developed to generate appropriate methods and materials for the early education of children with special needs. Contains an added Individualized family service plan (IFSP).